CASE REPORT: HEMICHOREA-HEMIBALLISMUS IN NON-KETOTIC HYPERGLYCEMIA AND NON-HEMORRHAGIC STROKE PATIENT WITH BASAL GANGLIA HYPERDENSITY - Regina Caecilia Setiawan; William Septian Sonyo; Luh Kadek Trisna Lestari (The Indonesia Neurological Association Branch of Denpasar, 2019)
Background : Hemichorea-hemiballismus (HC-HB) is a hyperkinetic disorder characterized by uncontrolled movements, non patterned, occurring mostly in the proximal extremity on one side of the body. The etiology that most often causes HC-HB is acute cerebrovascular disorder. Non-ketotic hyperglycemia is another etiology that is very important because it is the second most common cause of HC-HB and can be manifested as an initial symptom or complication of diabetes mellitus. This case is rare and the prevalence is unknown. Case : A diabetic patient with non-ketotic hyperglycemia reported with hemiballismus syndrome. A 60-year-old woman experiences involuntary, repetitive, and non-rhythmic movements in the left arm and leg. These patients have a history of uncontrolled diabetes mellitus and hypertension. Head CT scan images in patients showed hyperdensity lesions in the right basal ganglia which were thought to be caused by non-ketotic hyperglycemia and infarction in the right temporal lobe. Involuntary movements improve after blood glucose targets are achieved by administering basal and prandial insulin. Clinical response in the case of hemiballismus above is reversible even though the appearance of hyperdensityt lesions can last for several months. Discussion : Hemichorea-Hemiballismus (HC-HB) is a rare disorder of involuntary movement, most often caused by focal lesions in the basal ganglia and the contralateral subthalamic nucleus. HC-HB is mainly caused by systemic processes both focal and diffuse. Nonketotic hyperglycemia is known to be a metabolic cause of HC-HB, especially in elderly patients with uncontrolled diabetes mellitus. Clinical manifestations and supporting patients support hyperglycemia and basal ganglia hyperdensity to be the etiology of hemiballismus experienced by patients. Conclusion : Many etiologies can cause this disorder, but vascular disorders and non-ketotic hyperglycemia are the most common etiologies. HC-HB in non-ketotic hyperglycemic is manifestation which is very rare in diabetes mellitus. The prognosis is quite good in most patients with or without treatment. This case report describes a successful treatment approach with positive results and a fairly short duration. Keywords: Hemichorea, Hemiballismus, Hyperglycemia, Basal Ganglia Hyperdensity